Nitric Oxide and Decreases in Resistance Exercise Blood Pressure With Aerobic Exercise Training in Older Individuals - Otsuki, Takeshi; Nakamura, Fumiko; Zempo-Miyaki, Asako (Frontiers in Physiology, 2019)
An exaggerated blood pressure response to resistance exercise is a marker of masked hypertension and a risk factor for future essential hypertension. Habitual aerobic exercise decreases systolic blood pressure (SBP) during resistance exercise in older individuals, but the underlying mechanisms have not been explored. This study tested the hypothesis that nitric oxide (NO) mediates a reduction of resistance exercise SBP with aerobic training in older individuals. Normotensive older adults participated in a 6-week program as a part of the aerobic training group (n=23, exercised for an average of 4.4 d/wk and 59 min/d) or the control group (n=26, asked not to modify their lifestyle during the experimental period). The aerobic exercise intervention increased plasma concentrations of nitrite/nitrate (NOx, end product of NO) and deceased SBP during a one-hand arm curl exercise at 20% and 40% of one-repetition maximum and brachial-ankle pulse wave velocity (an index of arterial stiffness). In the control group, there were no differences in these measures before and after the experimental period. Changes in plasma NOx concentrations during the study period were correlated with changes in resistance exercise SBP. Stepwise regression revealed that changes in plasma NOx concentrations during the experimental period are a significant factor of changes in resistance exercise SBP, independent of age, sex, and changes in serum lipid profile, maximal oxygen uptake, resting SBP, and other variables. These results suggest that NO is associated with decreases in resistance exercise SBP with aerobic training in older individuals and help us better understand why habitual aerobic exercise prevents cardiovascular disease.